Hydrogen-induced mineral alteration: A review in the context of underground hydrogen storage (UHS) in saline aquifers - Heather Braid; Kevin Taylor; Edward Hough; Chris Rochelle; Vahid Niasar; Lin Ma (Earth-Science Reviews, 2024)

A guide to the otoliths of Southern Ocean lanternfishes (Myctophidae) - Darren W. Stevens; Heather E. Braid; Laureline Meynier; Pablo C. Escobar-Flores; Matthew H. Pinkerton; Doug Hopcroft; Yanyu He; Yves Cherel (Polar Biology, 2024)

Cryptic biodiversity in the commercial diamondback squid Thysanoteuthis rhombus Troschel 1857 - Diego Deville; Souta Mori; Kentaro Kawai; Alejandro Escánez; Armando Macali; Fedor Lishchenko; Heather Braid; Jean Githaiga-Mwicigi; Kolliyil S. Mohamed; Kathrin S. R. Bolstad; Kazutaka Miyahara; Chikatoshi Sugimoto; et al. (Reviews in Fish Biology and Fisheries, 2024)

Trophic ecology of the deep‐sea squid Moroteuthopsis ingens (Cephalopoda: Onychoteuthidae) from the Chatham Rise, Aotearoa New Zealand - Laura E. McBride; Heather E. Braid; Darren W. Stevens; Kathrin S. R. Bolstad (New Zealand Journal of Marine and Freshwater Research, 2023)
Cephalopods form important components of marine trophic systems worldwide, including those in the South Pacific. Moroteuthopsis ingens (Onychoteuthidae) is one of the most abundant deep–sea squids in the Aotearoa New Zealand region and is preyed upon by predators such as the sperm whale and orange roughy. However, despite the many publications on M. ingens ’ diet, knowledge on its feeding ecology remains limited. In this study, we analysed the prey of M. ingens from the Chatham Rise (an ecologically and economically important region east of Te Waipounamu/New Zealand's South Island) using DNA barcoding and otolith identification. Lanternfishes (Myctophidae) were the most frequently encountered prey item, but other teleost species, cephalopods and crustacean fragments were also found, indicating opportunistic and likely cannibalistic feeding behaviour. Five fish species (including a possibly undescribed species of Gymnoscopelus ) and Bathyteuthis abyssicola are reported as prey items of M. ingens for the first time. Moroteuthopsis ingens appears to be a component of several dynamic food chains and likely plays an important role in the transfer of carbon throughout marine environments in the Southern Hemisphere.

Two new ‘bottletail squids’ (Cephalopoda: Sepiadariidae: Sepioloidea) from New Zealand, with new observations on Sepioloidea pacifica (Kirk, 1882) - Jaever M. Santos; Kathrin S. R. Bolstad; Heather E. Braid (Marine Biodiversity, 2022)

Zoogeographic patterns of pelagic oceanic cephalopods along the eastern Pacific Ocean - Christian M. Ibáñez; Heather E. Braid; Sergio A. Carrasco; David A. López‐Córdova; Gabriela Torretti; Patricio A. Camus (Journal of Biogeography, 2019)
Aim To analyse the diversity and distribution of oceanic pelagic cephalopods along the eastern Pacific Ocean assessing the existence of biogeographic structuring, and the role of physical variables in generating geographical patterns. We hypothesized that the control by environmental factors, and the effect of geometric constraints, determine the range size and limits of distribution of oceanic cephalopods along the eastern Pacific Ocean, generating a latitudinal gradient in species richness. Location Eastern Pacific Ocean (60°N – 60°S), from the Gulf of Alaska to the Southern Ocean. Methods Based on a literature review and >5,000 records obtained from collections, we constructed a presence–absence matrix including 61 latitudinal bands (2° each) along the Eastern Pacific, and estimated species richness and range endpoints at each band. Biogeographic units were determined by means of multivariate analyses. Species richness was compared with null model predictions in order to test for the existence of geometric constraints using the Mid‐Domain Null model. The effects on species richness of environmental variables (temperature, salinity and oxygen) were evaluated separately for surface and depth (0–1,000 m) data, by means of ordinary least squares regression and simultaneous autoregressive models. Rapoport's pattern was assessed by applying the Stevens’ method and the range midpoint method. Results Species richness was high across the tropics and decreased towards the both poles. We identified five biogeographic units, highlighting two major distribution breaks at 40°N and 42°S. Species richness was strongly related with environmental variables, although the combined variables accounted for a large fraction of the variance between 0 and 1,000 m ( R 2 = 0.99), while temperature was the best single predictor at the surface ( R 2 = 0.98). Species richness curves showed a mid‐domain effect (MDE), and the mean latitudinal range was higher in the tropics and at warm latitudes, generating an inverse Rapoport's pattern. Main conclusions Along the eastern Pacific Ocean oceanic cephalopods exhibit both a clear biogeographic patterning and an interhemispheric (poleward decreasing) diversity gradient, which appear strongly related with physical factors and external forcing, as well as with a MDE as a seemingly consequence of the naturally bounded domain of the Eastern Pacific.

Metal composition of arrow squid (Nototodarus sloanii [Gray 1849]) from the Chatham Rise, New Zealand: implications for human consumption - Alexandra Lischka; Chris J. Pook; Kathrin S. R. Bolstad; Jennifer L. Pannell; Heather E. Braid (Environmental Science and Pollution Research, 2019)

One step closer to understanding the chiroteuthid families in the Pacific Ocean - Heather E. Braid; Tsunemi Kubodera; Kathrin S. R. Bolstad (Marine Biodiversity, 2017)

Resolving the taxonomic status of Asperoteuthis lui Salcedo-Vargas, 1999 (Cephalopoda, Chiroteuthidae) using integrative taxonomy - Heather E. Braid (Marine Biodiversity, 2017)

Molecular phylogenetic analysis of the squid family Mastigoteuthidae (Mollusca, Cephalopoda) based on three mitochondrial genes - Heather E. Braid; Paul D. McBride; Kathrin S. R. Bolstad (Hydrobiologia, 2014)

A Common View of the Opportunities, Challenges, and Research Actions for Pongamia in Australia - Helen T. Murphy; Deborah A. O’Connell; Gary Seaton; R. John Raison; Luis C. Rodriguez; Andrew L. Braid; Darren J. Kriticos; Tom Jovanovic; Amir Abadi; Michael Betar; Heather Brodie; Malcolm Lamont; et al. (BioEnergy Research, 2012)

Preying on commercial fisheries and accumulating paralytic shellfish toxins: a dietary analysis of invasive Dosidicus gigas (Cephalopoda Ommastrephidae) stranded in Pacific Canada - Heather Elizabeth Braid; Jonathan Deeds; Stacey Lea DeGrasse; John James Wilson; Josephine Osborne; Robert Harland Hanner (Marine Biology, 2012)

Species on the menu of a generalist predator, the eastern red bat ( Lasiurus borealis ): using a molecular approach to detect arthropod prey - ELIZABETH L. CLARE; ERIN E. FRASER; HEATHER E. BRAID; M. BROCK FENTON; PAUL D. N. HEBERT (Molecular Ecology, 2009)
One of the most difficult interactions to observe in nature is the relationship between a predator and its prey. When direct observations are impossible, we rely on morphological classification of prey remains, although this is particularly challenging among generalist predators whose faeces contain mixed and degraded prey fragments. In this investigation, we used a polymerase chain reaction and sequence‐based technique to identify prey fragments in the guano of the generalist insectivore, the eastern red bat ( Lasiurus borealis ), and evaluate several hypotheses about prey selection and prey defences. The interaction between bats and insects is of significant evolutionary interest because of the adaptive nature of insect hearing against echolocation. However, measuring the successes of predator tactics or particular prey defences is limited because we cannot normally identify these digested prey fragments beyond order or family. Using a molecular approach, we recovered sequences from 89% of the fragments tested, and through comparison to a reference database of sequences, we were able to identify 127 different species of prey. Our results indicate that despite the robust jaws of L. borealis , most prey taxa were softer‐bodied Lepidoptera. Surprisingly, more than 60% of the prey species were tympanate, with ears thought to afford protection against these echolocating bats. Moths of the family Arctiidae, which employ multiple defensive strategies, were not detected as a significant dietary component. Our results provide an unprecedented level of detail for the study of predator–prey relationships in bats and demonstrate the advantages which molecular tools can provide in investigations of complex ecological systems and food‐web relationships.